Padlet as Media to Improve Writing Mastery of English Department Students of Uniska 2015-2016 - Lestari, Pritantina Yuni; Kurniawan, Erwin Hari (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2018)
Multimedia has been spread out and used by many students in their live, but it is rarely to use multimedia as one of media used in teaching learning process. The objective of this study is to know whether the use of Padlet as media can improve studentsâ descriptive writing mastery of students of English Department of Uniska in the third semester. The research design used is Classroom Action Research consisting of two cycles. Each cycles consisted of three opportunities for students to have interaction using Padlet. The cycle consisted of planning, implementing, observing and reflecting. The instruments used in this research were observation check list and writing test using Padlet. Padlet was introduced from the first time of teaching learning process in the class and the following interactions were using Padlet without having direct interaction in the classroom. The first cycle was not successful because of the students got difficulty in managing time in accessing Padlet and some errors in their grammatical used. Then in the second cycle, the result showed that 18 from 20 students passed the minimum score and all students did all assignment using Padlet. From the result, it can be concluded that the implementation Padlet as media can improve studentsâ writing mastery. Keywords: Padlet, writing mastery, descriptive writing